The transnational feminist movement in the Americas in the 1930s - Álvarez Giménez, María Elvira (Ciencia Nueva, revista de Historia y Política, 2019)
This paper aims to study how a transnational feminist movement emerged in the Americas and had a significant period of activity in the 1930s. It examines its goals and political strategies, as well as the impact of collective mobilization. Mobilizing collectively at the transnational and international level allowed feminists from the American continent to gain some victories as well as political legitimacy. We will see how mobilizing collectively at the continental level served them as a strategy of struggle to acquire symbolic or material resources. At times, it increased the legitimacy of feminism that feminists were unable to obtain in their countries. The detour by the international was therefore extremely useful to them to put pressure on their governments. Besides, they did not conceive of their struggles in isolation. They believed that in order to obtain civil and political rights, but also the maintenance of peace on the continent, they had to build a collective struggle that transcended their borders.